PEMBUATAN TERMOSTAT CERDAS TANGGAP PERUBAHAN CUACA BERBASIS IOT UNTUK HIDROPONIK SISTEM WICK PADA TANAMAN PAKCOY - Damayanti, Ni Luh Putu Riana; Wirawan, I Gede Putu Wirarama Wadashwara; Jatmika, Andy Hidayat (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2023)
Hydroponics is an agricultural cultivation that uses water as a growing medium. One of the plants that can be cultivated hydroponically is the pakcoy plant. Pakcoy is a plant with an optimum water temperature range for its growth which is 15-30°C. The process of stabilizing the water temperature is important because the optimal temperature will make plant growth good. Currently, the process of monitoring and stabilizing water temperature is done manually and the process is carried out periodically so it is not easy to do. Therefore, the authors conducted a study to design an IoT-based intelligent thermostat for wicking hydroponic systems for pakcoy plants. The intelligent thermostat system consists of a DS18B20 water temperature sensor, a Peltier cooling system, and a water pump and uses the MQTT data communication protocol. This research was conducted with 3 stages of testing, namely, black box testing, Peltier calibration testing, and the final stage of testing which is divided into 2, namely without using a website and using a website. The final stage of testing is carried out in the morning, afternoon, evening, night, and early morning with the results of the system testing working to stabilize the water temperature when there is a temperature change of up to 2°C and then stabilized periodically to a tolerance of 1°C. So it can be concluded that the system in this study belongs to the category of a good system and is feasible to use.